STRATEGI SUPERVISI PENGAWAS UNTUK MENINGKATKAN MUTU PEMBELAJARAN - Suherman Suherman (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2017)
The purpose of this research is to know the planning strategy, implementation and evaluation strategy of supervision of school supervisor. The method used in the form of descriptive qualitative analysis on Disdikpora environment with data collection techniques in the form of interviews, study documentation and observation. Data sources consist of supervisors, principals and teachers. Research findings: (1) The supervision planning strategy contains five elements, i.e.: identifying school profiles and determining supervision missions; Conducting environmental analysis; Formulating indicators of success; Determine the goals and objectives of supervision, and create a supervision program; (2) The implementation strategy of supervision, contains three elements, i.e.: measuring performance; Comparing performance to established standards; And correct deviations from the standard by corrective action; (3) The supervision evaluation strategy contains six elements, i.e.: formulating evaluation objectives; Develop evaluation tools; Implement evaluation tools; Processing the results of the evaluation; Summarizes the results of the evaluation, and follow-up.